(untitled) (International Journal of Food and Nutritional Sciences, 2024)
The world is moving beyond the imagination of the people, now most of the preference is given to the technology which should be efficient and simple to use and should be used by the users who have just basic knowledge about the technology. The method of security and sharing should be improved. Coming to the wi-fi credentials sharing windows doesn’t support any QR sharing even though manual sharing is allowed it is difficult to remember the complex textual passwords and it is difficult to enter manually who have basic knowledge. We can give best alternative for the password sharing by using the graphical representation which uses QR encryption which can be easily scannable by any other devices during the connection. Our aim is to simply the wi-fi password sharing in windows environment which uses QR encryption.